A Label-Free, Quadruplex-Based Functional Molecular Beacon (LFG4-MB) for Fluorescence Turn-On Detection of DNA and Nuclease - Hu, Dan; Huang, Zhenzhen; Pu, Fang; Ren, Jinsong; Qu, Xiaogang (Chemistry : a European journal, 2011)
We demonstrate a novel concept for the construction of a label‐free, quadruplex‐based functional molecular beacon (LFG4‐MB) by using G‐quadruplex motif as a substitute for Watson–Crick base pairing in the MB stem and a specific G‐quadruplex binder, N‐methyl mesoporphyrin IX (NMM) as a reporter. It shows high sensitivity in assays for UDG activity/inhibition and detection of DNA sequence based on the unique fluorescence increase that occurs as a result of the strong interaction between NMM and the folded quadruplex upon removal of uracil by UDG or displacement of block sequence by target DNA. The LFG4‐MB is simple in design, fast in operation and could be easily transposesd to other biological relevant target analysis by simply changing the recognition portion. The LFG4‐MB does not require any chemical modification for DNA, which offers the advantages of simplicity and cost efficiency and obviates the possible interference with the affinity and specificity of the MB as well as the kinetic behavior of the catalysts caused by the bulky fluorescent groups. More importantly, the LFG4‐MB offers great extent of freedom to tune the experimental conditions for the general applicability in bioanalysis. Better by the quarter: A unique quadruplex‐based, label‐free functional molecular beacon (LFG4‐MB) has been constructed for sensitive, facile and real‐time assaying of UDG activity and inhibition and detection of a DNA sequence by using a G‐quadruplex motif as a substitute for Watson–Crick base pairing in the MB stem and a specific G‐quadruplex binder, N‐methyl mesoporphyrin IX (NMM) as a fluorescent reporter.